Flavonoids and isoflavonoids from Gynerium sagittatum - Benavides, Angelyne; Bassarello, Carla; Montoro, Paola; Vilegas, Wagner [UNESP]; Placente, Sonia; Pizza, Cosinio (Elsevier B.V., 2007)
Four flavonoids namely (2R,3R)-2,3-trans-7,4 '-dimethoxydihydroflavonol, (2R,3S,4S)-2,3-trans-3,4-cis-7,4'-dimethoxy-3,4-flavandiol, 6-hydroxy-7,4 '-dimethoxyflavone, 6,7,4 '-trimethoxyflavone, along with the known isoflavonoids ferreirin, dihydrocajanin, dalbergioidin, dihydrobiochanin A and biochanin A and other I I known compounds were isolated from the roots of Gynerium sagittatum. The structural characterization of these compounds was carried out via one- and two-dimensional NMR experiments in combination with ESI-MS. Finally a quantitative analysis of the isoflavones of the methanolic extract was performed by LC-ESI-MS. The high quantity of isoflavonoids found in G. sagittatum makes this plant a good natural source of isoflavonoids. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Gynerium sagittatum; Poaceae; flavanones; flavandiols; flavones; isoflavonoids